Allelopathic Impact of Sorghum and Sunflower on Germinability and Seedling Growth of Cotton (Gossypium hirsutum L.) - Muhammad Nawaz Kandhro; Habib-ur-Rehman Memon; Mahmood Laghari; Abdul Wahid Baloch; Muhammad Ali Ansari (Journal of Basic & Applied Sciences, 2016)
Sorghum and sunflower are considered as highly allelopathic plants with inhibitory efficacy on plants of other species. In a pot study, the phytotoxic potential of sorghum and sunflower shoot and root on germination and seedling growth of cotton was evaluated through soil incorporation of powders and spray of water extracts. The experiment was conducted at | department of Agronomy, Sindh Agriculture University Tandojam during Kharif (summer) 2010 and 2011. The analysis of pooled data suggested that all the powders and water extracts of both allelopathic crops caused substantial suppression of germination and related traits of cotton seedlings as compared to control (untreated). Sorghum shoot powder (10 g kg-1 soil) caused highest allelopathic effects and reduced cotton seed germination by 12.8%, root length by 45.4%, shoot length by 51.9%, fresh weight seedling-1 by 41.7% and dry weight seedling-1 by 36.7%, followed by sunflower shoot powder (10 g kg-1 soil) in phytotoxic efficiency for inhibiting seed germination, seedling growth and weight in contrast to control (untreated). Sorghum showed superiority over sunflower in allelopathic efficiency. Powder of both crops was found more allelopathic in contrast to water extract. Among plant parts phytotoxic potential, shoot proved higher in inhibitory effect than root. However, it was concluded from the results of present study that both sorghum and sunflower possess allelopathic compounds with growth suppressing ability which could be utilized for effective weed management in cotton under field conditions as eco-friendly low-cost alternate of herbicides with wise strategy.